Peter Eisenman. Decostruzione. InCubo della forma - Pisciella, Susanna (Scenari, 2021)
Thirty years after the famous Deconstructivist Architecture exhibition organized at New York Moma by P. Johnson and M. Wigley, Deconstructivism still inhabits the built landscape and its persistence invites for reflection. The article traces the manifesto and the theoretical premises of the exhibition and it investigates the discourse which was originally rejected by the curators. It acknowledges to P. Eisenman and to the contribution of J. Derrida the deeper reasons for the permanence of Deconstructionism, i.e. the codification of a new paradigm in architecture, the Hebrew one, whose way of living is unexplored. The “dislocation” is protected by an articulated encryption project, that requires a slow exegesis of the Eisenmanian writings “what I write serves as a disguise for my thinking”.